Duration of Mechanical Ventilation in an Adult Intensive Care Unit after introduction of Sedation and Pain Scales - Williams, T; Martin , S.; Leslie, Gavin; Thomas , L.; Leen, T.; Tamaliunas, S.; Lee, K.Y.; Dobb, G (American Association of Critical Care Nurses, 2008)
Sedation and analgesia scales promote a less-distressing experience in the intensive care unit and minimize complications for patients receiving mechanical ventilation. To Evaluate outcomes before and after introduction of scales for sedation and analgesia in a general intensive care unit. A before-and-after design was used to evaluate introduction of the Richmond Agitation-Sedation Scale and the Behavioural Pain Scale for patients receiving mechanical ventilation. Data were collected for 6 months before and 6 months after training in and introduction of scales.Sedation and analgesia scales did not reduce duration of ventilation in an Australian intensive care unit.